We say we are doing primary health care but we're not: Remote area nurses' perspectives on the challenges of providing primary health care services. Issue 5 (October 2021) - McCullough, Kylie; Bayes, Sara; Whitehead, Lisa; Williams, Anne; Cope, Vicki
Abstract: Background: Nurses are essential in global strategies to improve population health. However, there is a paucity of research that describes the application of primary health care from a nursing perspective. Australian remote area nurses work in primary health care clinics which are often the only health care service within the community. Services include acute care response as well as health promotion and public health activities. Question, Hypothesis or Aim: To explore the meaning and application of primary health care principles from the perspective of nurses in Australian remote settings. Methods: Telephone interviews were conducted with registered nurses and nurse practitioners working in Australian remote settings using constructivist grounded theory methods during 2014 and 2015. Findings: Nurses in remote settings considered primary health care to be an holistic social model of care that included caring for the community as well as the individual. However, they were unable to provide care consistent with their intention due to the resource-poor nature of the remote setting. Inadequate physical resources, limited specialist health services, and a lack of time were found to impact on remote area nurses' abilities to provide primary health care. Discussion: This study is unique in its description of a cause of remote area nurse stress as being the inability to provide primary health care in line with their expectations. Conclusion: Appropriate resourcing is essential for nurses to be able to provide a comprehensive array of holistic services in line with community-identified need that also reflect their own definitions of primary health care.